Knowledge work compulsion: The neoliberal mediation of working existence in the network society - Hofmeyr, A. B. (South African journal of philosophy, 2023)
This contribution seeks to understand the pervasive phenomenon of work compulsion among knowledge workers in our present network society. Knowledge workers not only have to work all the time from anywhere, but they also appear to want to. This study argues that this curious phenomenon may be attributed to the thumotic satisfaction that knowledge work generates. What is more, the neoliberal theory of human capital has found a way to harness thumotic satisfaction to the profit incentive, and has created arguably the most productive working subject to date. The argument is divided into four parts: First, the paper analyses the government(- ality) of control operative in the network society by defining "neoliberalism". It then focuses on Foucault's examinations of German and American neoliberalism in the 20th century, treating them as instances of governmentality. The aim is to assess whether employing a governmentality lens is a valid approach for critically analysing present-day neoliberalism. If it proves justifiable, which I argue it does, the study explores the potential valuable insights gained from examining contemporary neoliberalism through this particular analytical framework. Second, the study turns to the "spiritedness" of knowledge workers under the conditions of stealth control that typify the neoliberal network society. Curiously, these highly engaged workers have reportedly experienced increased overall well-being. However, their overinvestment in work appears to be disproportionate to absolute necessity, increased earnings or improved overall quality of life. This paper contends that work compulsion generates and is in turn fuelled by thumotic satisfaction. Third, the study tries to ascertain the connection between neoliberal governmentality and thumos. Neoliberal governmentality appears to have found a way to appropriate thumotic satisfaction to produce and sustain the competitive entrepreneurial spirit. The fourth part of the study considers how the knowledge worker might resist the compulsion to work incessantly.